(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This research seeks to investigate the essential correlation between the meticulous selection of Quranic vocabulary and the realization of structural unity in Quranic discourse through an applied rhetorical examination of the expression "recites unto them" (yatlu ’alayhim) within its Quranic framework. The study adopts a descriptive analytical approach, grounded in classical rhetorical frameworks and modern linguistic scholarship. The findings demonstrate that every Quranic lexical element is deliberately chosen to establish comprehensive textual coherence and holistic structural unity, with the expression "recites unto them" serving as a compelling manifestation of this relationship through its deep rhetorical significance and its integral association with core prophetic responsibilities.